2009
DOI: 10.1364/oe.17.012502
|View full text |Cite
|
Sign up to set email alerts
|

Real-time microscopic imaging of esophageal epithelial disease with autofluorescence under ultraviolet excitation

Abstract: Detection of esophageal disease in current clinical practice is limited to visualization of macroscopic epithelial morphology. In this work, we investigate high resolution autofluorescence imaging under ultra violet excitation to visualize microscopic epithelial changes related to disease progression using a bench top prototype microscope. The approach is based on the hypothesis that UV excitation light can only penetrate the superficial layer of cells resulting in autofluorescence images of the epithelial lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…27 It has recently been demonstrated that AF microscopy under UV excitation provides visualization of cellular morphology and organization in ex vivo esophagus specimens without the use of contrast agents or tissue preparation. 28 Due to the Same as above, with nuclear atypia not extending to surface.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…27 It has recently been demonstrated that AF microscopy under UV excitation provides visualization of cellular morphology and organization in ex vivo esophagus specimens without the use of contrast agents or tissue preparation. 28 Due to the Same as above, with nuclear atypia not extending to surface.…”
Section: Introductionmentioning
confidence: 93%
“…30 Our preliminary results indicated that microstructure morphology and superficial nuclear and cellular organization can be imaged in real-time, providing immediate information related to the presence and progress of early-stage abnormalities, such as BE and dysplasia, that originate in the superficial epithelial mucosa before developing into cancer. 28 Further development of this method necessitates the establishment of optical rules for recognizing cellular patterns (the rules for interpretation) that correspond to normal and abnormal histologies spanning from early benign modifications (Barrett's esophagus) to subsequent dysplastic change and progression toward carcinoma. Optical rules of disease interpretations that can be accepted by the medical community as an analogous guideline to traditional methods would provide the key to enabling in vivo histopathologic evaluation in the operating room.…”
Section: Optical Imaging Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate this parameter space, we have developed a prototype experimental multimodal microscope system (MMS) 22 and determined that wavelengths shorter than 355 nm penetrate only the superficial layer of cells, resulting in acquisition of high contrast AF images of the epithelial layer of unprocessed tissue specimens (no contrast agents or tissue preparation) using wide-field microscopy. 23,24 It was also found using ex vivo human esophageal tissue biopsy specimens under 266-nm excitation resulted in the best image contrast arising mainly from tryptophan emission and its nonuniform distribution within the cells. 25 It was postulated that imaging the epithelial layer with this method would provide more specific histopathologic information related to the disease.…”
Section: Introductionmentioning
confidence: 98%